McManus in love [videorecording (DVD)] - McManus, Patrick F.; Behrens, Tim, 1937-2017 (Penguin Productions, 2007)
In this play, Pat defeats his fear of the dark and then realizes it was nothing compared to his fear of girls. What follows is a delightful look at what all people go through as they begin to date.